Enhancing Cyber Security in the Banking Sector Using Biometrics - Richa Singh (International Journal of Wireless Security and Networks, 2026)
The fast-paced digital evolution within the banking industry has led to a substantial rise in the number of financial transactions conducted through online and mobile platforms. While this transformation has improved customer convenience and service accessibility, it has also exposed banking systems to a wide range of cyber threats, such as identity theft, phishing attacks, credential compromise, and financial fraud. Conventional authentication mechanisms, including passwords and personal identification numbers (PINs), are no longer sufficient to provide robust security due to their susceptibility to guessing, reuse, and social engineering attacks. Consequently, biometric authentication has gained prominence as a dependable and secure solution for enhancing cybersecurity within banking systems. This research paper presents a comprehensive analysis of biometric authentication systems used in the banking sector, focusing on fingerprint recognition, iris scanning, facial recognition, and voice authentication. The study evaluates these biometric modalities based on accuracy, cost of implementation, maintenance requirements, usability, and resistance to spoofing attacks. Advanced security mechanisms such as liveness detection, biometric template protection, advanced encryption standard (AES) encryption, and multi-factor authentication frameworks are examined to address challenges related to data breaches and unauthorized access. Furthermore, the paper discusses regulatory and ethical considerations associated with biometric data handling, including data privacy, user consent, and compliance with national and international data protection laws. Through comparative analysis and real-world banking use cases, this research identifies suitable biometric solutions for both large-scale and small banking institutions. The findings indicate that biometric authentication significantly enhances transaction security and customer trust when implemented with strong encryption, regulatory compliance, and ethical data management practices. The study concludes by highlighting future research directions involving artificial intelligence-driven biometric systems and decentralized security architectures to further strengthen digital banking security.
Keywords: Banking security; Biometric Authentication; Cyber security; Encryption; Liveness Detection; data privacy